Brewing Resistance: Indigenous Knowledge and the Contestation of Colonial Powers Through Value Chains for Coffee—A Literature Review - Cano-González, Katherine; Quinones-Ruiz, Xiomara F. (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
Through a literature review, we examine how Indigenous Knowledge (IK) is addressed in studies of value chains (VCs) for coffee and the types of knowledge recognized. We undertake a decolonial critique of capitalocentric paradigms, prioritizing place-based ontologies and relational socioecological practices to rethink coffee quality and value creation. Indeed, “quality” and “value” are grounded in the lived experiences of those who sustain the land—Indigenous and peasant communities. Actors’ epistemologies sustain coffee VCs through context-specific responses to systemic, epistemic, and ideological crises while asserting governance models for their well-being alongside dominant frameworks. Although research on coffee VCs has been extensive, it rarely engages these knowledge systems through a decolonial lens. Consequently, the political and epistemic significance of place-based and relational knowledge in shaping coordination mechanisms—such as quality and value—remains insufficiently theorized and empirically overlooked. Emerging interdisciplinary research on actors’ positionalities frames VCs not as neutral commodity exchanges but as contested political arenas where situated knowledge systems actively reshape and re-signify the value of coffee. This paper moves beyond listing Indigenous practices or diagnosing the still-colonial industry structures. It demonstrates how IK-based practices constitute situated responses to coloniality’s multiple dimensions. Therefore, we foreground not only critique but agency, as observed in agroecological practices, narratives of cultural identity, community-based governance, or cooperative management.